1998
DOI: 10.1038/bjc.1998.726
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of human malignant brain tumour cell line proliferation by anti-urokinase-type plasminogen activator monoclonal antibodies

Abstract: Summary A brain tumour-associated marker, urokinase (UK), was investigated using rabbit anti-UK polyclonal and munne anti-UK monoclonal antibodies, which were prepared by immunization with low molecular weight UK (LMW-UK) and high molecular weight urokinase (HMW-UK) synthetic peptide respectively. The polyclonal antibody cross-reacted with both LMW-UK and HMW-UK. whereas the murne MAbs were specific for HMW-UK. These immunological probes were used to study urokinase in glioma extracts, tissues, sera and cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Irrelevant MAbs of the same isotype and concentrations showed no effects on the proliferation of the breast cancer, normal human lymphocyte and liver cell lines. Our results were consistent with those reported by other investigators [3,35,37]. At this stage, it is unclear to us how anti-UK-MAbs lyse the breast cancer cells.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Irrelevant MAbs of the same isotype and concentrations showed no effects on the proliferation of the breast cancer, normal human lymphocyte and liver cell lines. Our results were consistent with those reported by other investigators [3,35,37]. At this stage, it is unclear to us how anti-UK-MAbs lyse the breast cancer cells.…”
Section: Discussionsupporting
confidence: 83%
“…Very recently Abaza et al [35] reported the inhibition of proliferation of human malignant brain tumor cell lines by anti-UK MAbs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations